CORE CURRICULUM AND MINIMUM ACADEMIC STANDARDS (CCMAS) IMPLEMENTATION IN NIGERIAN UNIVERSITIES: PROBLEMS AND PROSPECTS - Nuhu , Ummul Qulsum; Imoukhuede , O. G. (Multi-Disciplinary Research and Development Journals Int’l, 2025)
In 2022 the National Universities Commission (NUC) introduced the Core Curriculum and Minimum Academic Standards (CCMAS) to modernize and harmonize undergraduate programmes across Nigerian universities. CCMAS establishes common learning outcomes, specifies programme credit ranges, and requires that at least 70% of each programme consist of core courses while allowing 30% institutional flexibility for locally relevant or innovative content. This chapter explains the conceptual basis of CCMAS, clarifies implementation terminology, evaluates key impediments to rollout (funding deficits, inadequate infrastructure including power and ICT, academic staff shortages, and capacity gaps), and highlights institutional and policy prospects (NUC leadership, professional-body engagement, international assistance, and targeted capacity building). Drawing on implementation theory and practice, I argue that successful CCMAS deployment requires coordinated financing, phased infrastructure investments, comprehensive faculty retraining, monitored resource verification, and stakeholder buy-in. The chapter ends with practical recommendations — a national CCMAS implementation fund, prioritized resource verification and electrification/ICT plans, scalable faculty development programmes, incentives for staff retention, and stronger monitoring and evaluation — designed to make CCMAS an engine for graduate employability and national development. The analysis draws on NUC’s CCMAS documents and other recent policy sources to link expectations to realistic operational steps.